Clinical application of short tandem repeat polymorphism analysis in the differential diagnosis of early hydatidiform mole and hydropic abortion - J. Wang; S.W. Chen; X.Y. Qin; X.Z. Zheng; P. Wang; X.Y. Cai (IMR Press, 2020)
Objective: To determine the clinical differential diagnosis value of short tandem repeat polymorphism (STR) analysis in early hydatidiform moles (HMs) and non-molar gestations. Methods: Four hundred eighty-one patients with suspected HMs were examined using traditional pathology methods and STR analysis. The value of the STR method in distinguishing HMs from non-molar gestations was evaluated. Results: Among 481 patients with suspected HMs, 177 were diagnosed with HMs and 304 with non-molar gestations based on histopathologic examination. The STR genotypic results show that 151 patients were diagnosed with HMs, including 63 complete HMs and 88 partial HMs. Three hundred thirty patients were diagnosed with non-molar gestations, including 43 patients with chromosome abnormalities. Among 63 complete HMs, 56 were monosyllabic and 7 were dispermic. All 88 partial HMs were dispermic. The histopathologic diagnoses in 84 patients were not in agreement with STR analyses. Among the 84 cases, 29 were incorrectly diagnosed with non-molar gestations and the others were incorrectly diagnosed with HMs by histopathologic examinations. The chi-test result demonstrated that the two methods were quite different. Conclusion: STR polymorphism analysis is a rapid, simple, and accurate method that can be utilized for accurate diagnosis of early HMs and hydropic abortions.